Organophotocatalytic Radical–Polar Cross-Coupling of Styrylboronic Acids and Redox-Active Esters - Brals, Jeremy; D’Arcy-Evans, Nicholas; McGuire, Thomas M.; Watson, Allan J. B. (Synlett, 2023)
We report the development of a radical–polar cross-coupling reaction using styrylboronic acids and redox-active esters under organophotoredox catalysis. The reaction proceeds through a formal polarity-mismatched radical addition. The use of an organic photocatalyst permitted very low loadings of the electron-shuttle additive and accelerated reaction times compared with established processes. The scope of the reaction was explored, and the utility of the products is demonstrated.
Keywords: esters; styrylboronic acids; photocatalysis; radical–polar cross-coupling